Sistem Pendukung Keputusan Rekomendasi Pemilihan Notebook Dengan Metode Weighted Product Berbasis Web - Prianggara, Prayuda; , Hernawan Sulistyanto, S.T., M.T (2017)
Choosing notebook has become a hassle since numerous manufacturers are producing various types of computers with different specifications. Therefore, the potential buyers feel confused and spent a lot of time to learn about the options in the market before purchase. The purpose of this study was to develop a Decision Support System Recommendations for assisting the selecting Notebook with Web-Based Weighted Product evaluation method that allows prospective buyers to make informed decisions.Use the programming language of PHP (Hypertext Preprocessor) and MySQL was used as the database. Weighted product methods use multi-criteria decision analysis to connect rating attributes, where each attribute rating should be raised to improve the attribute weights leading to best ranking of the alternatives resulting in selecting the best product. Testing system based on the results of trials with Black Box methods and questionnaire's result of application testing. Alternatively, the output also can be final suggestion of multiple options to provide flexibility in choosing the notebook based on the criteria entered by the user.